Model railway speed controller / Mohd Nizam Abdul Razak and Shahar Jaafar - Abdul Razak, Mohd Nizam; Jaafar, Shahar (1992)
The motor speed controller circuit to be described was developed for use with 00 gauge model railway engines. However it can be easily modified to control any other small 12V DC motor such as in a minidril1. circuit achieves "closed loop" The control of motor speed by measuring the back-EMF of the motor. This gives excellent speed regulation at all speeds and reduce "stiction" when starting. A single potentiometer controls both speed and direction. Alternatively a speed control and separate reversing switch can be incorporated. The controller has lacthing over—load protection,